Not applicable - Bin Huwaidin, Mohamed; Antwi-Boateng, Osman (Journal of Regional Security, 2021)
Dear Editor: Please find enclosed our manuscript entitled “THE RISE OF CHINA AS A HEGEMONIC POWER: THE CASE FOR A PARTIAL PEACEFUL RISE,” which we request you to consider for publication as an original research article in Journal of Regional Security This study investigates the rise of China as a hegemonic power. It discusses tensions primarily between China and the United States (US), which is currently seen as having the leading world power, with predictions of a possible future confrontation or war between the two countries. This is based on historical cases of wars between rising powerful nations and ruling nations in the past. This study resolves that China is rising partially peacefully and will continue to do so in order to avoid antagonizing the US, with which it is interdependent in certain regards. This manuscript has not been published elsewhere and is not under consideration by another journal. We have approved the manuscript and agree with submission to Journal of Regional Security. There are no conflicts of interest to declare. We believe that the findings of this study are relevant to the scope of your journal and will be of interest to its readership. The manuscript has been carefully reviewed by an experienced editor whose first language is English and who specializes in editing papers written by scientists whose native language is not English. We look forward to hearing from you at your earliest convenience. Sincerely, Osman Antwi-Boateng, PHD (Corressponding Author). Associate Professor of Political Science & International Relations, United Arab Emirates University, Al Ain, UAE. Email Address: antwiboateng@gmail.com